2000
DOI: 10.1209/epl/i2000-00135-4
|View full text |Cite
|
Sign up to set email alerts
|

Confinement effects on the chain conformation in thin polymer films

Abstract: The chain conformation of thin polymer films was investigated via diffuse neutron scattering. The samples consist of blend films of protonated and deuterated polystyrene spin coated onto glass substrates. A variation of the thickness of the blend films in a range of about 41 down to 0.66 times the radius of gyration R g of the chains in the bulk enables the determination of film thickness and confinement effects. With diffuse neutron scattering in a reflection geometry the chain conformation in thin polymer fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
112
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(126 citation statements)
references
References 22 publications
13
112
1
Order By: Relevance
“…In such studies, the results have been mixed; some studies have found no change in the radius of gyration in the plane of the surface for polymethyl methacrylate on glass, 25 and polystyrene on hydrogen-passivated silicon, 26 while others have found a significant lengthening for polystyrene on glass. 27,28 A very detailed and precise study on nanoscale silica with no agglomeration exhibited no changes in chain dimensions upon the addition of filler. 29 This latter paper critically examined the literature and concludes that with proper conditions, in particular monodisperse chains, then no chain extension should occur.…”
Section: Reviewmentioning
confidence: 99%
“…In such studies, the results have been mixed; some studies have found no change in the radius of gyration in the plane of the surface for polymethyl methacrylate on glass, 25 and polystyrene on hydrogen-passivated silicon, 26 while others have found a significant lengthening for polystyrene on glass. 27,28 A very detailed and precise study on nanoscale silica with no agglomeration exhibited no changes in chain dimensions upon the addition of filler. 29 This latter paper critically examined the literature and concludes that with proper conditions, in particular monodisperse chains, then no chain extension should occur.…”
Section: Reviewmentioning
confidence: 99%
“…The bond orientational order parameter was calculated as S B,i ¼ 0.5 [3/cos 2 y j,z S i À 1], where y is the angle made by the bond between beads j and j À 1 with z axis and /yS represents the ensemble average taken over all segments of a single chain i. As expected [31][32][33][34]37,38 , S B becomes B0 in the bulk for the thicker films, but retains a small but noticeable value even in the bulk for the thinnest film simulated.…”
mentioning
confidence: 99%
“…According to their reported work, change in the T g is attributed to the change in the viscosity of the PS phase. The enrichment of nanoparticles at interfaces between the polymeric blend phases has also been found in numerical simulations [1,2,7,8] that indicate that there may be an accumulation of the nanoparticles at the phase interfaces with similar energetic interaction of nanoparticles for both polymer phases. In the present study it appears that this energetic interaction between respective polymer phases and nanoparticles is of van der waal type interaction that restricts the mobility of polymer chains and thus more energy is required by the system to achieve the glass transition state and therefore an increase in glass transition temperature of that particular polymeric phase in respective nanocomposite series, is observed.…”
Section: Glass Transition Temperature Measurementsmentioning
confidence: 60%
“…Since PS/PMMA blend systems are immiscible, the incorporation of the CdS nanoparticles with different composition dependent morphological blend structures present tailored tensile properties. Bonding between nanoparticles and polymer matrix leads good adhesion between matrix and filler [8] leading to higher density of nanocomposite structure. In this way compactness of composite is directly related to their respective prominent elastic properties.…”
Section: Thermal Conductivity Measurementsmentioning
confidence: 99%
See 1 more Smart Citation